An electro-rheological study of the nematic liquid crystal 4-n-heptyl-4'-cyanobiphenyl - Cidade, M. T. (2010)
An experimental and theoretical study of the electro-rheological effects observed in the nematic phase of 4-n-heptyl-4'-cyanobiphenyl has been conducted. This liquid crystal appears to be a model system, in which the observed rheological behaviour can be interpreted by the Leslie-Ericksen continuum theory for low molecular weight liquid crystals. Flow curves are illustrated at different temperatures and under the influence of an external electric field ranging from 0 to 3 kV mm-1, applied perpendicular to the direction of flow. Also presented is the apparent viscosity as a function of temperature, over similar values of electric field, obtained at different shear rates. A master flow curve has been constructed for each temperature by dividing the shear rate by the square of the electric field and multiplying by the square of a reference value of electric field. In a log-log plot, two Newtonian plateaux are found to appear at low and high shear rates, connected by a shear-thinning region. We have applied the Leslie-Ericksen continuum theory, in which the director alignment angle is a function of the electric field and the flow field boundary conditions are neglected, to determine viscoelastic parameters and the dielectric anisotropy.